A Rice Ca2+ Binding Protein Is Required for Tapetum Function and Pollen Formation . Issue 3 (23rd September 2016) - Yu, Jing; Meng, Zhaolu; Liang, Wanqi; Behera, Smrutisanjita; Kudla, Jörg; Tucker, Matthew R.; Luo, Zhijing; Chen, Mingjiao; Xu, Dawei; Zhao, Guochao; Wang, Jie; Zhang, Siyi; et al.
Abstract : OsDEX1 binds Ca 2   + and plays a conserved role in the development of tapetal cells and pollen formation in rice. Abstract: In flowering plants, successful male reproduction requires the sophisticated interaction between somatic anther wall layers and reproductive cells. Timely degradation of the innermost tissue of the anther wall layer, the tapetal layer, is critical for pollen development. Ca 2+ is a well-known stimulus for plant development, but whether it plays a role in affecting male reproduction remains elusive. Here we report a role of Defective in Exine Formation 1 (OsDEX1) in rice ( Oryza sativa ), a Ca 2+ binding protein, in regulating rice tapetal cell degradation and pollen formation. In osdex1 anthers, tapetal cell degeneration is delayed and degradation of the callose wall surrounding the microspores is compromised, leading to aborted pollen formation and complete male sterility. OsDEX1 is expressed in tapetal cells and microspores during early anther development. Recombinant OsDEX1 is able to bind Ca 2+ and regulate Ca 2+ homeostasis in vitro, and osdex1 exhibited disturbed Ca 2+ homeostasis in tapetal cells. Phylogenetic analysis suggested that OsDEX1 may have a conserved function in binding Ca 2+ in flowering plants, and genetic complementation of pollen wall defects of an Arabidopsis ( Arabidopsis thaliana ) dex1 mutant confirmed its evolutionary conservation in pollen development. Collectively, these findings suggest that OsDEX1 plays a fundamental role in the development of tapetal cells and pollen formation, possibly via modulating the Ca 2+ homeostasis during pollen development.